2017
DOI: 10.1007/s00484-017-1462-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the climatic potential for tourism in Iran through biometeorology clustering

Abstract: This study presents a spatiotemporal analysis of bioclimatic comfort conditions for Iran using mean daily meteorological data from 1995 to 2014, analyzed through Physiological Equivalent Temperature (PET) index and Universal Thermal Climate Index (UTCI) indices, and bioclimatic clustering. The results of this study demonstrate that due to the climate variability across Iran during the year, there is at any point in time a location with climatic condition suitable for tourism. Mean values demonstrate maxima in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…Yang et al [20] examined the spatial differentiation of China's summer tourist destinations based on the UTCI and tourism resources data and analyzed climatic suitability. Roshan [21] also presented a spatiotemporal analysis of bioclimatic comfort conditions for Iran and demonstrated that there is, at any point in time, a location with climatic conditions suitable for tourism. A new method based on defining comfortable calendar days was proposed to identify regions thermally suitable for sunbird tourism and their comfortable periods in China [22].…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al [20] examined the spatial differentiation of China's summer tourist destinations based on the UTCI and tourism resources data and analyzed climatic suitability. Roshan [21] also presented a spatiotemporal analysis of bioclimatic comfort conditions for Iran and demonstrated that there is, at any point in time, a location with climatic conditions suitable for tourism. A new method based on defining comfortable calendar days was proposed to identify regions thermally suitable for sunbird tourism and their comfortable periods in China [22].…”
Section: Introductionmentioning
confidence: 99%
“…The clustering analysis implies the Euclidean distance and Ward's D analysis method. 37 The weather data include daily temperatures and relative humidity from 1995 to 2014. The methodology includes the creation of 19…”
Section: Methodsmentioning
confidence: 99%
“…Meteorological conditions are key factors in many areas of human activity such as agriculture, transport, power engineering, insurance and risk assessment [1], industrial and marketing planning [2], tourism, sport, mass events [3,4], national security, and many more where atmospheric conditions may have a direct or indirect impact [5][6][7][8]. Besides the financial and safety relevance of meteorological and hydrological datasets [9], this kind of information is very often crucial to reliably answer a scientific problem [10], which heavily relies on the quality of meteorological dataset used in this kind of research.…”
Section: Introductionmentioning
confidence: 99%